HARMONI: a single-field, wide-band, integral field spectrograph for the European ELT - Thatte, N; Tecza, M; Clarke, F; Davies, R; Remillieux, A; Bacon, R; Lunney, D; Arribas, S; Mediavilla, E; Gago, F; Bezawada, N; Ferruit, P; et al. (2010)
We describe the results of a Phase A study for a single field, wide band, near-infrared integral field spectrograph for the European Extremely Large Telescope (E-ELT). HARMONI, the High Angular Resolution Monolithic Optical and Nearinfrared Integral field spectrograph, provides the E-ELT's core spectroscopic requirement. It is a work-horse instrument, with four different spatial scales, ranging from seeing to diffraction-limited, and spectral resolving powers of 4000, 10000 and 20000 covering the 0.47 to 2.45 μm wavelength range. It is optimally suited to carry out a wide range of observing programs, focusing on detailed, spatially resolved studies of extended objects to unravel their morphology, kinematics and chemical composition, whilst also enabling ultra-sensitive observations of point sources. We present a synopsis of the key science cases motivating the instrument, the top level specifications, a description of the opto-mechanical concept, operation and calibration plan, and image quality and throughput budgets. Issues of expected performance, complementarity and synergies, as well as simulated observations are presented elsewhere in these proceedings[1]. © 2010 Copyright SPIE - The International Society for Optical Engineering.